Design and synthesis of novel hydroxypyridinone derivatives as potential tyrosinase inhibitors. Issue 13 (1st July 2016) - Zhao, De-Yin; Zhang, Ming-Xia; Dong, Xiao-Wu; Hu, Yong-Zhou; Dai, Xiao-Yan; Wei, Xiaoyi; Hider, Robert C.; Zhang, Jin-Chao; Zhou, Tao
Graphical abstract: Abstract: Two groups of novel hydroxypyridinone derivatives6 (a –e ) and12 (a –c ), were designed as potential tyrosinase inhibitors, and synthesized using kojic acid as a starting material. The tyrosinase inhibitory activity of these two groups was demonstrated to be potent, especially compounds6e and12a, whose IC50 values for monophenolase activity were 1.95 μM and 2.79 μM, respectively. Both of these values are lower than that of kojic acid (IC50 = 12.50 μM). Compounds6e and12a were investigated for the inhibitory effect on diphenolase activity. The results showed that the inhibitory mechanism of these two compounds was reversible and that the inhibitory type was a competitive-uncompetitive mixed-type. The values of IC50 of6e and12a on the diphenolase activity of tyrosinase were determined to be 8.97 μM and 26.20 μM, respectively. The inhibitory constants ( K I and K IS ) of6e were determined as 17.17 μM and 22.09 μM, respectively; and the K I and K IS values of12a were 34.41 μM and 79.02 μM, respectively. Compound6e showed a greater ability to reduce copper and a stronger copper chelating ability than kojic acid.